Conjugative transposition of Tn916 requires the excisive and integrative activities of the transposon-encoded integrase. - Storrs, M J (1991)
Transposon Tn916 is a 16.4-kb broad-host-range conjugative transposon originally detected in the chromosome of Enterococcus faecalis DS16. Transposition of Tn916 and related transposons involves excision of a free, nonreplicative, covalently closed circular intermediate that is substrate for integration. Excisive recombination requires two transposon-encoded proteins, Xis-Tn and Int-Tn, whereas the latter protein alone is sufficient for integration. Here we report that conjugative transposition of Tn916 requires the presence of a functional integrase in both donor and recipient strains. We have constructed a mutant, designated Tn916-int1, by replacing the gene directing synthesis of Int-Tn by an allele inactivated in vitro. In mating experiments, transfer of Tn916-int1 from Bacillus subtilis to E. faecalis was detected only when the transposon-encoded integrase was supplied by trans-complementation in both the donor and the recipient. These results suggest that conjugative transposition of Tn916 requires circularization of the element in the donor followed by transfer and integration of the nonreplicative intermediate in the recipient.